A comparison of the effects of electroacupuncture versus transcutaneous electrical nerve stimulation for pain control in knee osteoarthritis: a Bayesian network meta-analysis of randomized controlled trials. Issue 3 (June 2021) - Shi, Xiaowei; Yu, Wenjing; Zhang, Wei; Wang, Tong; Battulga, Oyunerdene; Wang, Lijuan; Guo, Changqing
Background: To compare the effectiveness of electroacupuncture (EA) and transcutaneous electrical nerve stimulation (TENS) for pain control in knee osteoarthritis (KOA). Methods: Four English (MEDLINE, EMBASE, Cochrane Library and Web of Science) and three Chinese (China Science Journal Citation Report (VIP), Wanfang and China National Knowledge Infrastructure (CNKI)) language databases were searched for eligible randomized controlled trials (RCTs), comparing four approaches: EA, TENS, medication and sham/placebo controls. The primary outcome was pain intensity, measured by visual analogue scale (VAS), numeric-rating scale (NRS) or Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scale. Classic pairwise and Bayesian network meta-analyses were conducted to integrate the treatment efficacy/effectiveness through direct and indirect evidence. Results: Thirteen studies were included. In the direct meta-analyses, there was no statistically significant overall effect of EA (mean difference (MD) −4.77, 95% confidence interval (CI) −12.51 to 2.96), while the overall effects of high-frequency transcutaneous electrical nerve stimulation (H-TENS) (MD −16.63, 95% CI −24.57 to −8.69) and medication (MD −7.12, 95% CI −12.07 to −2.17) were statistically significant. In the network meta-analyses, the relative effect of the EA and H-TENS groups (MD 5.07, 95% CI −11.33 to 21.93) on pain control did not differ. Meanwhile, H-TENS demonstrated the highest probability of being the first best treatment, and EA had the second highest probability. Conclusion: The present analysis indicated that both EA and TENS exert significant pain relieving effects in KOA. Among the four treatments, H-TENS was found to be the optimal treatment choice for the management of KOA pain in the short-term, and EA the second best treatment option. Given that the application of TENS is recommended by various international guidelines for the treatment of KOA, EA may also represent a potentially effective non-pharmacologic therapy.